Genome-wide identification, evolution of Krüppel-like factors (klfs) and their expressions during GCRV challenge in grass carp (Ctenopharyngodonidella). (July 2021) - Chen, Liangming; Huang, Rong; Li, Yangyang; Li, Yangyu; Li, Yongming; Liao, Lanjie; He, Libo; Zhu, Zuoyan; Wang, Yaping
Abstract: The Krüppel-like factors (KLFs) are a family of transcription factors containing three highly conserved tandem zinc finger structures, and each member participates in multiple physiological and pathological processes. The publication of genome sequences and the application of bioinformatics tools have led to the discovery of numerous gene families in fishes. Here, 24 klf genes were re-annotated in grass carp. Subsequently, the number of klf family members were investigated in some representative vertebrate species. Then, a series of bioinformatics analysis showed that grass carp klfs in the same subfamily had similar genome structure patterns and conserved distribution patterns of motifs, which supported their molecular evolutionary relationships. Furthermore, the mRNA expression profiles showed that 24 grass carp klfs were ubiquitously expressed in 11 different tissues, and some of them displayed tissue-enriched expression patterns. Finally, the expressions of the evolutionarily expanded klf members ( klf2a, 2b, 2l, 5a, 5b, 5l, 6a, 6b, 7a, 7b, 11a, 11b, 12a, 12b, 15 and 15l ) during GCRV infection were also analyzed. The results suggested that grass carp klf genes with common evolutionary sources may share functional diversity and conservation. In conclusion, this study provides preliminary clues for further researches on grass carp klf members and their underlying transcriptional regulatory mechanisms during GCRV infection. Highlights: Krüppel-like factor ( klf ) gene family was re-annotated and characterized in grass carp ( Ctenopharyngodon idella ) . Similar genome structures and conservative motif patterns support evolutionary relationship among grass carp klfs. Grass carp klfs were ubiquitously expressed, and some of them displayed characteristics of tissue enrichment. The evolutionarily expanded klfs exhibited different mRNA levels in immune-relevant tissues during GCRV infection.